2022
DOI: 10.1155/2022/1169614
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Cell Transcriptome Analysis Reveals the Importance of IRF1/FSTL1 in Synovial Fibroblast Subsets for the Development of Rheumatoid Arthritis

Abstract: Objectives. This study aimed to investigate the potential role of synovial fibroblasts (SFs) in the development of rheumatoid arthritis (RA) to identify potential molecular targets and provide a theoretical basis for the treatment of RA. Methods. GSE109449, a fibroblast transcriptome dataset of synovial tissue from RA and osteoarthritis (OA), were obtained from the GEO database. After standard cell quality control, this single-cell transcriptome data was used to perform routine single-cell analysis processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…IRF1 can induce TLR3 expression in pristane-induced arthritis ( 66 ). A recent study demonstrated that the invasiveness of synovial fibroblasts is regulated by the expression of follistalin-like protein 1 induced by IRF1 ( 142 ).…”
Section: Irfsmentioning
confidence: 99%
“…IRF1 can induce TLR3 expression in pristane-induced arthritis ( 66 ). A recent study demonstrated that the invasiveness of synovial fibroblasts is regulated by the expression of follistalin-like protein 1 induced by IRF1 ( 142 ).…”
Section: Irfsmentioning
confidence: 99%
“…1 As inflammation is a central process contributing to symptoms and disease progression in arthritis, IRF family proteins have been studied in joint tissues, underscoring their roles in activating immune cells and producing inflammatory cytokines. 2 During the pathogenesis of rheumatoid arthritis, IRF1 mediates the expression of tumor necrosis factor-induced genes in endothelial cells 3 and fibroblast-like synoviocytes, 4,5 contributing to the recruitment of macrophages and the initiation of inflammatory processes in mice. 6 Osteoarthritis (OA) is the most common form of arthritis, mainly characterized by progressive degeneration of articular cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of IL-17 signaling pathway in chondrocytes could inhibit the overexpression and activation of key proteins, such as IL-17RA, ACT1 and TRAF6, which could improve the occurrence of cartilage inflammation in OA. Research has shown that aryl hydrocarbon receptor (AHR), caveolin-1 (CAV1), c-reactive protein (CRP), C-X-C motif chemokine 2 (CXCL2), interferon regulatory factor-1 (IRF1), secreted phosphoprotein 1 (SPP1) and other targets are key targets in the pathogenesis of arthritis ( Chen et al, 2022 ; Wang et al, 2022 ; Sakthiswary et al, 2022 ; Zhu et al, 2022 ; Li et al, 2023 ; Yang et al, 2023 ), but role of them in the treatment of arthritis by CC has not been verified and further clarification is needed.…”
Section: Introductionmentioning
confidence: 99%